Contemporary outcomes of lower extremity vascular repairs extending below the knee: A multicenter retrospective study. Issue 1 (July 2016) - Fortuna, Gerald; DuBose, Joseph J.; Mendelsberg, Ranan; Inaba, Kenji; Haider, Ansab; Joseph, Bellal; Skarupa, David; Selleck, Matthew J.; O'Callaghan, Thomas A.; Charlton-Ouw, Kristofer
Abstract : OBJECTIVES: To determine the outcomes of vascular injury interventions extending below the knee. METHODS: Vascular injury repairs extending below the knee from January 2008 to December 2014 were collected from six American College of Surgeons Level I trauma centers. Demographics, management, and outcomes were collected and analyzed. RESULTS: A total of 194 vascular injuries were identified. The mean age was 33.7 years, with 88.1% male, and 71.1% had blunt injury. Admission systolic blood pressure was less than 90 mm Hg in 10.8%; prehospital tourniquets were used in 5.6%. Median mangled extremity severity score (MESS) was 6.0 [interquartile range, 6]. Imaging used included computed tomography angiography (58.2%) and angiography (7.2%); with 66 (34.0%) proceeding directly to OR based on examination alone. Vascular interventions were conducted primarily by vascular (66.0%) and trauma (25.3%) surgeons at a median time from injury of 8 hours (interquartile range, 7 hours). Initial interventions included graft interposition (57.7%) with saphenous vein (111) or synthetic graft (1), primary repair (14.9%), endovascular stent-graft (1.5%), and patch angioplasty (2.1%). Fasciotomy was performed at initial operation in 41.8%, and for delayed compartment syndrome in 2.1%. Vascular reintervention was required in 20 patients (6.7%) for bleeding (seven patients) or thrombosis (13 patients). There was a higher reintervention rates for thrombosis among interposition grafts with distal anastomotic sites at the below-knee popliteal compared to those extending to the tibioperoneal trunk or distal trifurcation vessels, but this was not significant. (4/60, 6.7% vs. 6/49, 12.2%; p = 0.34 ). Postintervention amputation rates were significantly higher among interposition grafts extending distal to the popliteal (4/60 [6.7%] vs. 15/49 [30.6%]; p = 0.006). CONCLUSIONS: The management of vascular injuries extending below the knee remains a complex issue of extremity trauma care. The need for delayed amputation is significantly more common when revascularization below the distal popliteal artery is required. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III; therapeutic/care management study, level IV.